Social insects - Sutherland, Jonathan (Milwaukee, WI Gareth Stevens Publishing, 2007)
Features small creatures that live in nests, hives, and mounds, such as the army ant, dung beetle, and bee-killer wasp.
Elementary
Keywords: Insects; Insect societies; Nature's Monsters